Credit Risk Spreads in Local and Foreign Currencies - Wiener, Zvi (IMF Working Papers; Working Paper, 2009)
The paper shows how-in a Merton-type model with bankruptcy-the currency composition of debt changes the risk profile of a company raising a given amount of financing, and thus affects the cost of debt. Foreign currency borrowing is cheaper when the exchange rate is positively correlated with the return on the company's assets, even if the company is not an exporter. Prudential regulations should therefore differentiate among loans depending on the extent to which borrowers have "natural hedges" of their foreign currency exposures.